Social Media and the Public Sphere - Christian Fuchs (tripleC: Communication, Capitalism & Critique)
Social media has become a key term in Media and Communication Studies and public discourse for characterising platforms such as Facebook, Twitter, YouTube, Wikipedia, LinkedIn, Wordpress, Blogspot, Weibo, Pinterest, Foursquare and Tumblr. This paper discusses the role of the concept of the public sphere for understanding social media critically. It argues against an idealistic interpretation of Habermas and for a cultural-materialist understanding of the public sphere concept that is grounded in political economy. It sets out that Habermas’ original notion should best be understood as a method of immanent critique that critically scrutinises limits of the media and culture grounded in power relations and political economy. The paper introduces a theoretical model of public service media that it uses as foundation for identifying three antagonisms of the contemporary social media sphere in the realms of the economy, the state and civil society. It concludes that these limits can only be overcome if the colonisation of the social media lifeworld is countered politically so that social media and the Internet become public service and commons-based media.